Advances in the management of cardioembolic stroke associated with patent foramen ovale. (9th February 2022) - Mac Grory, Brian; Ohman, E Magnus; Feng, Wuwei; Xian, Ying; Yaghi, Shadi; Kamel, Hooman; Reznik, Michael E
ABSTRACT: Patent foramen ovale (PFO) describes a valve in the interatrial septum that permits shunting of blood or thrombotic material between the atria. PFOs are present in approximately 25% of the healthy population and are not associated with any pathology in the vast majority of cases. However, comparisons between patients with stroke and healthy controls suggest that PFOs may be causative of stroke in certain patients whose stroke is otherwise cryptogenic. Options for the diagnosis of PFO include transthoracic echocardiography, transesophageal echocardiography, and transcranial Doppler ultrasonography. PFOs associated with an interatrial septal aneurysm seem to be more strongly linked to risk of recurrent stroke. Therapeutic options for secondary stroke prevention in the setting of a PFO include antiplatelet therapy, anticoagulation, and percutaneous device closure. Recent randomized clinical trials suggest that percutaneous closure reduces the subsequent risk of stroke in appropriately selected patients, with a large relative benefit but small absolute benefit. Referral for percutaneous PFO closure should therefore be considered in certain patients after a multidisciplinary, patient centered discussion. Areas for future study include structural biomarkers to aid in determining the role of PFO closure in older people with possible PFO associated stroke, the role of direct oral anticoagulants, and very long term outcomes after device closure.